MEMPUNYAI ATAU MEMUNYAI ATAU ADA YANG LAIN LAGIKAH? KAJIAN MORFOLOGI - Perangin-angin, Esra; Ningsih, Wahyu; Ginting, Sri Dinanta Beru (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
The use of language is certainly not free from errors and these errors vary. It is through the analysis of language errors that the form of language errors that are made both morphologically, phonologically, and syntactically can be explained which then provide certain benefits for the communication process. The term language error has various meanings. The first letter of KTSP does not melt if the second letter is consonant.Exceptions to this rule (denoted by an * in the examples below) are prefix combinations on- with a prefix root word p which is followed by a consonant. In this combination, letters p melt to smooth pronunciation and prevent double letters p nearby.According to Sugiyono (2010: 15) the qualitative research method is a research method based on the philosophy of postpositivism, used to research on natural object conditions (the opposite is experiments) with researchers as the key instrument for sampling and data carried out purposively and snowball, data collection techniques with triangulation (combined), data analysis is inductive or qualitative, and the results of qualitative research emphasize the process of forming affixes and meanings. Sutama (2012: 32) states that qualitative research is more directed at understanding social phenomena from the perspective of participants (making theory). Instagram poll quiz out of 200 people who saw the Instagram poll quiz, only 66 people took part in the poll quiz, around 33% participated. Of the 66 people who took the Instagram poll quiz,around 35 people (53%) chose 'argument/right', 31 people (47%) chose 'argument/right'.